Understanding umbilical venous catheter insertion practices through a prospective multicenter observational study. (12th December 2022) - Patel, S.; Shannon, D.; Eldridge, W.; El-Ters, N.; Hanford, J.; Walker, T.; Scheer, A.; Jones, E.; Linwood, K.; Aragon, N.; Dunscombe, L.; Gerbes, J.; et al.
Abstract: Objective: To understand practices of umbilical venous catheter (UVC) insertion in tertiary level neonatal intensive care units (NICU) and investigate the outcomes of subsequent attempts following a failed initial attempt. Study design: Prospective, multi-center observational study of UVC insertions at tertiary level NICUs between March 2019 and January 2020. Results: Of the 101 UVCs inserted at 4 centers, seventy-two (71%) were central at the first attempt and 50% were central at subsequent attempts. Patients with at least 1 failed attempt at insertion were less likely to have a centrally placed UVC ( p = .009). Manipulations were less likely to be required when UVC was centrally placed during the first attempt. Maneuvers such as posterior liver mobilization used during insertion were likely to be associated with successful central placement of UVC ( p = .0243). The time to complete the procedure was significantly less when the UVC was central at the first attempt (34.2 ± 20.2 vs 46.9 ± 33.8) ( p = .0292). Gestational age, birth weight, and age of the baby at the insertion of the UVC, experience of the provider, and type of catheter were comparable among groups. The Shukla formula was most commonly used by providers to measure the depth of UVC placement. Conclusion: Repetitive attempts and manipulations were less likely to be beneficial in the successful central placement of UVC in neonates. Additionally, repetitive attempts at insertion prolonged the overall duration of the procedure.